1985
DOI: 10.1017/s0033291700020924
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of the effects of lithium on thyroid function and on the prevalence of antithyroid antibodies

Abstract: SynopsisTests of thyroid function and pathology were carried out on 133 patients before they were treated with lithium (Li+). Of the 12 patients who subsequently became hypothyroid during treatment with lithium 9 had, before the commencement of treatment, thyroid autoantibodies and/or an exaggerated thyroid stimulating hormone (TSH) response to thyrotropin releasing hormone (TRH), whereas 3 patients had neither of these indicators. Lithium administration was accompanied by a rise in thyroid antibody titre in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…In contrast lithium inhibits the secretion of thyroid hormones from the thyroid gland, resulting in an increase in serum TSH (77,78) and thyroid autoantibodies (79), which in susceptible patients might lead to overt hypothyroidism (79). This effect of lithium might result in a decreased supply of thyroid hormones to the brain, which according to the presented hypothesis is inconvenient.…”
Section: Antidepressive Drugs -Effect On Thyroid Hormonesmentioning
confidence: 83%
“…In contrast lithium inhibits the secretion of thyroid hormones from the thyroid gland, resulting in an increase in serum TSH (77,78) and thyroid autoantibodies (79), which in susceptible patients might lead to overt hypothyroidism (79). This effect of lithium might result in a decreased supply of thyroid hormones to the brain, which according to the presented hypothesis is inconvenient.…”
Section: Antidepressive Drugs -Effect On Thyroid Hormonesmentioning
confidence: 83%
“…In vitro studies suggest that Li might exert an immunomodulatory activity through cAMP and/or phosphoinositol phosphate pathways [5], However, the relevance of these observa tions is unclear, since concentrations active in vitro great ly exceed therapeutic Li levels observed in vivo [26]. An alternative explanation is that the increase of serum TSH due to the antithyroid activity of Li could enhance the expression/release of thyroid autoantigens with conse quent exacerbation of thyroid autoimmunity in subjects with altered thyroid tolerance [27], If our assumptions are correct, differences in the prev alence of subtle underlying thyroid abnormalities in the patients examined could be responsible for the discrepant results reported by other investigators on serum thyroid autoantibodies during Li administration [10,II,28], Racial and geographical differences of the study popula tion as well as different methodological approaches in the initial diagnostic assessment and in follow-up may repre sent additional confusing factors.…”
Section: Discussionmentioning
confidence: 87%
“…Psychiatric patients on lithium (Li) therapy frequently develop goiter and/or hypothyroidism [1], These effects are commonly ascribed to the antithyroid activity of Li [2], but the possibility that this drug might trigger thyroid autoimmunity has also been suggested [3][4][5], However, the data supporting the latter hypothesis are scanty and contradictory; the prevalence of circulating antithyroid autoantibodies in patients on long-term Li therapy ranges from 14 to 50% in different investigations [6][7][8][9] and no conclusive data may be derived from the few longitudinal studies presently available [9][10][11][12], Differences in individ ual sensibility related to genetic heterogeneity and/or to underlying subclinical thyroid disease might explain the above discrepancies.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the majority of patients who developed hypothyroidism after lithium therapy have either thyroid peroxidase antibodies and/or an exaggerated stimulation of TSH [21,31,32]. Other studies showed fluctuations in antibody titers over the course of lithium treatment, negating the possibility that lithium increases these antibodies [33].…”
Section: Hypothyroidismmentioning
confidence: 99%